Calmodulin Is the Fundamental Regulator of NADK-Mediated NAD Signaling in Plants - Tai, Li; Li, Bin-Bin; Nie, Xiu-Min; Zhang, Peng-Peng; Hu, Chun-Hong; Zhang, Lu; Liu, Wen-Ting; Li, Wen-Qiang; Chen, Kun-Ming (Frontiers in Plant Science, 2019)
Calcium (Ca2+) signaling and nicotinamide adenine dinucleotide (NAD) signaling are two basic signal regulation pathways in organisms, playing crucial roles in signal transduction, energy metabolism, stress tolerance and various developmental processes. Notably, calmodulins (CaMs) and NAD kinases (NADKs) are important hubs for connecting these two types of signaling networks, where CaMs are the unique activators of NADKs. NADK is a key enzyme for NADP (including NADP+ and NADPH) biosynthesis by phosphorylating NAD (including NAD+ and NADH) and therefore, maintains the balance between NAD pool and NADP pool through an allosteric regulation mode. In addition, the two respective derivatives from NAD+ (substrate of NADK) and NADP+ (product of NADK), cyclic ADP-ribose (cADPR) and nicotinic acid adenine dinucleotide phosphate (NAADP), have been considered to be the important messengers for intracellular Ca2+ homeostasis which could finally influence the combination between CaM and NADK, forming a feedback regulation mechanism. In this review, we briefly summarized the major research advances related to the feedback regulation pathway, and provided new insights on the regulatory mechanism for CaM and NADK interactions during plant development and signaling. Furthermore, we genome-widely identified the members of wheat (Triticum aestivum L.) CaM family and initially proved the interactions between TaCaMs and TaNADKs at the molecular level, laying a foundation for further study in the regulation mechanism between CaMs and NADKs. All these results indicate that CaM is the fundamental regulator of NADK-mediated NAD signaling in plant development and stress response.